Probe Feed E-Shaped Patch Antenna at 4.87 GHz - Ezgi Kucuk; Burak Bayram; S. Taha Imeci; Tahsin Durak , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this paper, E-shape microstrip patch antenna for wireless communication is designed, simulated, built and tested. The operating frequencies of antenna are 2.97 GHz and 4.85 GHz, the substrate FR4 is used for proposed antenna with dielectric constant 4.01 and 1.7mm thickness. Two parallel slots are cut to perturb the surface current path to achieve dual resonance. The E-shape has return loss of -28 dB and -14.03 dB at operating frequencies 2.97 GHz and 4.85 GHz respectively. Designing and simulation of this antenna has been done by the help of Sonnet Software. This antenna is fed by a co-axial probe feeding. In this paper, the effects of length difference among antenna legs has been studied.